The adoption of electric vehicles in Dushanbe, Tajikistan - Shahboz Ashurzoda; Ahyahudin Sodri; Hayati Sari (Center for Science and Technology, IAIN Surakarta, 2024)
Switching from conventional fossil fuel vehicles to electric vehicles (EVs) offers a promising way to reduce carbon emissions, especially if we also decarbonize our electricity sources. This study focuses on Dushanbe, the capital of Tajikistan, where EV adoption is still in its early stages. Understanding local perceptions is crucial for making informed decisions to promote the use of EVs. There has been used a qualitative approach, gathering data through questionnaires from a diverse group of Dushanbe residents. The analysis showed varied perceptions as older respondents were more likely to agree with EV adoption, and there were notable differences based on gender and education level. Women showed greater enthusiasm for EVs, and those with a Master’s degree were more likely to support the transition. Residents recommended increasing salaries, improving infrastructure, and providing government support to make the shift to EVs easier. This study highlights the importance of understanding local views in shaping policies for sustainable transportation in Dushanbe. Further research and targeted actions are needed to overcome challenges and encourage widespread EV adoption.